A comparison of Main Central Thrust and other Himalayan fault systems from central and west Nepal with some two-dimensional stress fields - Dhital, Megh R (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 123-4